رسول اللہ ﷺ کی قبل از بعثت مواساتی سرگرمیاں، حلف الفضول کے تناظر میں ایک تحقیقی مطالعہ - Sumaira Safdar; Kalsoom Paracha (Pakistan Journal of Islamic Research)
Allah Almighty (SWT) had bestowed upon the Hazart Muhammad (ﷺ) the feelings of compassion, sorrow and grief of humanity. The result of this compassion was that before the Prophethood, at a very young age, which is usually immature, He (ﷺ) participated as a vanguard in the Ḥilf al Fudūl to the weak and the oppressed. The Hilf ul Fudool was, in fact, the establishment of an institution of justice in this ignorant society of the Arabs, the purpose of which was to prevent the tyrants from oppressing and to support the victims. In Arabs exploitation of the weak was considered as a sign of pride and strength. There was no organized force to stop the tyrants and bring justice to the victims. Agreements were made on the basis of tribal prejudice and raising voice against the tyrants was tantamount to declaring war on the whole tribe. The establishment of such an institution against this cruel and brutal practice was of paramount importance and the participation of the Hazrat Muhammad (ﷺ) indicates that even in his youth, His blessed heart was full of sympathy for the suffering humanity and the spirit of all kinds of sacrifices for the protection of their rights.